ARUS KAS OPERASIONAL, TINGKAT HUTANG DAN UKURAN PERUSAHAAN PADA PERSISTENSI LABA - Sri Supriyatna; Mulia Rahmah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
Analyze the effect of operating cash flow on profit persistence, debt level on profit persistence and company size on profit persistence as well as the effect of operating cash flow, debt level and company size on profit persistence simultaneously. Measurement of profit persistence using accounting profit before tax and future comprehensive income, operating cash flow using the operating cash flow statement (AKO), debt level using debt to assets ratio (DAR) and company size using the natural logarithm (Ln) of total assets. The sampling technique uses the purposive sampling method by considering certain criteria with a sample of 85 data samples. The data used is secondary data. The data analysis method uses descriptive statistical analysis and multiple regression analysis, processed using SPSS version 25. The sample in the research was 85 samples from 17 food and beverage sub-sector companies on the Indonesia Stock Exchange. Based on the test results, the R square coefficient value of the independent variable was 0.304 or 30.4%.The results of the regression test show that operating cash flow variables have a significant influence on profit persistence, while debt levels and company size do not have a significant effect on profit persistence. The results of simultaneous statistical tests show that the variables of operating cash flow, debt level and company size together simultaneously have a significant influence on profit persistence.